Contos populares e letramento literário na EJA: saberes e prazeres nos recontos de Ricardo Azevedo - Queiroz, Yara Carvalho Pedrosa de (2020)
Popular oral literature is an indispensable element in the study of the cultural traditions of a society. Starting from this perspective, Câmara Cascudo specifically considered the popular tale as the broadest and most expressive material of folklore, a true cultural catalyst that gathers historical, sociological, ethnographic and social information. Through his studies, Cascudo opened the way for several brazilian authors such as Monteiro Lobato, Mário de Andrade and Guimarães Rosa, who, inspired by popular culture, reinvented characters and stories told by ancestral voices. This work is also inspired by popular sources and aims to promote literary literacy in EJA cycle III classes (referring to the 6th and 7th grades), based on three oral tales rewritten by Ricardo Azevedo, writer and contemporary researcher, dedicated to the study of Brazilian culture. The object of our research, the tales “A quase morte de Zé Malandro”, “Coco verde e Melancia” and “Maria Gomes”, respectively from the works Contos de enganar a Morte, No meio da noite escura tem um pé de maravilha! e Contos de espanto e alumbramento present archetypal characters that well represent the playful, symbolic and humorous aspects present in popular culture. Our intervention aims to minimize the difficulties of textual comprehension presented by students and at the same time, to involve them in literary literacy practices through short stories. The choice of this genre was due to an identification of the students themselves with the elements of popular culture that like them, also needs appreciation and recognition. The accessible language, but rich in meanings present in the stories, signals the artistic nature of the literary text, making it possible for the student to associate pleasure with knowledge. For literacy issues, our work was based on Ferreiro and Teberosky (1984), Soares (1998) and on official documents such as LDB (2015), PCN (2001), PCN + (2002), Orientações Curriculares (2006) and BNCC (2017); for the study of popular literature, Cascudo (2004; 2006; 2010), Simonsen (1987), Leal (1985) and Azevedo (2007); for literary literacy, Candido (1995), Petit (2008; 2009) and especially Cosson (2006; 2009), in whom we methodologically support ourselves through the basic sequence.